Development Priorities in an Emerging Decentralized Economy: The Case of Armenia’s Local Development Programs - Mavisakalyan, Astghik (Springer, 2013)
Based on a data set of 217 communities in Armenia, this paperstudies the choice of priority directions in local development programs in theyears 2003–2005. The scope of programs is presented and discussed relative togood practices in local development. It is shown that a disproportionately highshare of programs is directed at improving local infrastructures, against theprinciples of good practices. Furthermore, the responsiveness to community needsof local development programs is explored for the case of drinking waterinfrastructure projects. This paper provides suggestive evidence for programresponsiveness, which further increases with an increase in newspaper circulationin a community.